Analisis Stabilitas dan Prediktabilitas Beta Saham pada Perusahaan Publik di Indonesia - Sukmadyasari, Narenda; Sutrisno, Sutrisno (TEMA, 2003)
Numerous studies examined the stability and predictability of stocks beta in some capital markets of some countries. However, there are few studies that applied in Indonesian capital market. The purpose of this study is to analysis the stability and predictability of stocks beta in Indonesia, both individual and portfolio betas. Before analyzing the stability and predictability of beta, the bias of beta must be corrected first by using four-lead and four-lag version of the Fowler and Rorke method. This study used weekly data of 162 stocks traded in Jakarta Stock Exchange (JSX) and composite index of JSX /IHSG as market return) from January 1, 2000 to December 31, 2002. The stability and predictability of beta were examined over three periods, each period consists of 52-week, by using transition matrices test and product-moment correlation test. Finally, the result from transition matrices test and product-moment correlation test shows that there is stability and predictability of portfolio betas over the research period in JSX but this result shows that individual betas are not predictable. Besides that, the result of this study shows that portfolio betas are more stable and predictable than individual betas. Keywords: beta bias, beta stability and predictability, lead and lag, transition matrices, product-moment correlation.